1972
DOI: 10.1002/ijch.197200022
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Reactions of Monomers with Conjugated Triple‐Bonds VII Mechanism of Transition from Monomer to Polymer Phase During Solid‐State Polymerisation

Abstract: The lattice‐controlled solid‐state polymerisation of three different modifications of 2,4‐hexadiin‐1,6‐diol‐bis(phenylurethane) was investigated by X‐ray and optical methods. The polymerisation is a homogeneous reaction. The polymer grows in the form of single chains within the crystal of the monomer. The chains extend along a definite crystallographic direction. Monomer and polymer are isomorphous and monomer‐polymer single crystals of various compositions are obtained up to a quantitative conversion in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

1974
1974
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Poly diacetylene. Solid state synthesis (Kaiser et al 1972, Baughman 1974) has recently been used to obtain polydiacetylenes of a high degree of structural per fection. This in turn has led to the measurement of a number of physical properties of this polymer (Stevens et al 1978) and several theoretical studies (Parry 1976, Boudreaux 1975, Cojan et al 1977, Wilson 1975, Philpott 1977 as well.…”
Section: Conjugated One and Two Dimensional Polymersmentioning
confidence: 99%
“…Poly diacetylene. Solid state synthesis (Kaiser et al 1972, Baughman 1974) has recently been used to obtain polydiacetylenes of a high degree of structural per fection. This in turn has led to the measurement of a number of physical properties of this polymer (Stevens et al 1978) and several theoretical studies (Parry 1976, Boudreaux 1975, Cojan et al 1977, Wilson 1975, Philpott 1977 as well.…”
Section: Conjugated One and Two Dimensional Polymersmentioning
confidence: 99%
“…16,97 However, a few exceptions are known for which it is observed that polymerization generates a polymer that is amorphous to X-rays after extraction of the remaining monomer: such a situation was encountered during the polymerization of 2,4-hexadiyne-1,6-diol 15 and during that of modification I of 2,4-hexadiyne-1,6-diol bis(phenylurethane). 26 Thus, it is possible that amorphization of poly-4 originates from the removal of the unreacted monomer. On the other hand, this observation is a clear indication that solid-state polymerization of 4 proceeds in a homogeneous manner.…”
Section: Solid-state Stability Ofmentioning
confidence: 99%
“…8,9 In case these interactions are ineffective at organizing suitably DA molecules in the crystal lattice, one way of solving the problem is to look for other polymorphs. 16,26 This solution is simple to implement, yet it does not always work and is hardly predictable. Alternatively, it is possible to use tools from the crystal engineer arsenal, especially cocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are polymorphic with different activities. Wegner (1969) and Kaiser et al, (1972) described three distinct forms for the 2,4 Aexadiyne 1,6 bis-(phenylurethane) (referred to as HDPU); this author has determined the lattice parameters of the form II, moderately reactive; we have recently indexed the powder data and we are beginning to resolve the structure of this HDPU form. The 2,4 Aexadiyne-1,6 bis-(/w-/olylurethane).…”
Section: Introductionmentioning
confidence: 99%